2004
DOI: 10.1097/01.cmr.0000129375.14518.ab
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent adjuvant radiotherapy and interferon-α2b for resected high risk stage III melanoma – a retrospective single centre study

Abstract: Interferon-alpha2b (IFNalpha2b) is the only form of systemic adjuvant therapy for stage III melanoma with documented survival benefit. Radiotherapy can also be utilized in the adjuvant setting in patients at high risk of nodal basin recurrence. As IFNalpha2b is associated with substantial toxicity, we sought to determine both the systemic and radiation-related toxicities in patients treated with combined adjuvant IFNalpha2b and regional adjuvant radiotherapy delivered in the setting of a single institution. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…A summary of these studies is described in Table 8. Several small retrospective studies have recently been reported on the role of concurrent radiotherapy or interferon or radiotherapy within 1 month of the delivery of interferon in resected high-risk melanoma [22][23][24][25]. These studies have generally reported locoregional control rates to be comparable with historical rates (Table 9).…”
Section: Discussionmentioning
confidence: 82%
“…A summary of these studies is described in Table 8. Several small retrospective studies have recently been reported on the role of concurrent radiotherapy or interferon or radiotherapy within 1 month of the delivery of interferon in resected high-risk melanoma [22][23][24][25]. These studies have generally reported locoregional control rates to be comparable with historical rates (Table 9).…”
Section: Discussionmentioning
confidence: 82%
“…Gyorki et al [29] report a group of patients (n = 18) who were treated concurrently with radiotherapy and IFNa2b, with a total dose of radiation ranging from 40-50 Gy and fractionation of 200-300 cGy; they found 50% grade III acute toxicities occurring in 44.4% of patients and grade III late toxicities in two patients, observing a correlation of acute/late toxicity with higher total dose of radiation (50 Gy). Nguyen et al [30] observed grade III acute toxicity (mucositis-dermatitis) at total radiation doses of 45, 41.4 and 59.4 Gy and 180 cGy doses per fraction respectively, in a subset of three patients with melanoma of the head and neck region, treated with concurrent radiation and IFNa2b.…”
Section: Discussionmentioning
confidence: 96%
“…The potential role of a radiosensitising effect of IFN and subsequent subacute or late toxicities when administered concurrently [17,[32][33][34], independently of the fraction size, has been previously described. Currently, the optimal sequence of radiation and IFN therapy is unknown.…”
Section: Discussionmentioning
confidence: 98%